The new demand of the economic policy in the field of economic security - Jílková, Eva; Štancl, Luboš (Management and Administration Journal, 2019)
The paper deals with problems of economic security. It provides a clear definition ofinternal and external factors of economic security which are based on the given economic environmentand have a direct impact on national security. Based on a clear identification of thesefactors, the aim of this paper is to determine the requirements for a modern safety-oriented economicpolicy, since it is obvious that due to current events in the world, new demands which are necessaryto be considered in order to maintain economic security are placed on the economic policy.